Follow the leader? A field experiment on social influence - Ambler, Kate; Godlonton, Susan; Recalde, Maria P. (Elsevier, 2021)
We conduct an artefactual field experiment in endogenously formed groups in rural Malawi to investigate social influence in risk taking. Treatments vary whether individuals observe the behavior of a formally elected leader, an external leader, or a random peer. Results show social influence in risk taking with differential influence by leader type. The decisions made by peers are most influential, followed by those made by formal leaders, and then external leaders. Exploratory analysis suggests that participants follow peers because they extract information from their choices and share risks with them; while other forms of social utility are gained from following the example of leaders.